Assessing knowledge about self-regulated learning: validation of a measurement tool for preschoolers - Grüneisen, Lena; Dörrenbächer-Ulrich, Laura; Kapsali, Efsevia; Perels, Franziska (Frontiers in Education, 2024)
Self-regulated learning (SRL), as the self-directed and goal-orientated control of one's learning process, is an important ability for academic success. Even at preschool age, when its development is at a very early stage, SRL helps to predict later learning outcomes. Valid test instruments are needed to identify preschoolers who require SRL support and help them to start school successfully. Therefore, the present study aimed to provide such a test instrument by revising and optimizing an existing strategy knowledge test and validating the revised version-the SRL Strategy Knowledge Test-in a sample of n = 104 German preschoolers (Mage = 5;11 years; 48.1% girls). For the validation, we used measures of (1) SRL and related constructs, (2) psychomotor development, and (3) academic competence, to determine three levels of validity: a) convergent, b) divergent, and c) criterion. All the correlation analyses controlled for child intelligence. The results showed that the test is of moderate difficulty and sufficiently reliable (Cronbach's α = .74), can generate normally distributed data, and has a one-factor structure. In line with our hypotheses, we found significant correlations for the convergent and criterion measures, and numerically smaller and insignificant correlations for divergent measures. The correlations for the criterion measures failed to be significant when controlling for intelligence. This may have been due to limitations in the measures used to examine criterion validity. The SRL Strategy Knowledge Test can be used in practice to diagnose the need for SRL support and in future studies and interventions on SRL development.